Peran Pemimpin Gereja dalam Memupuk Kerukunan Antaragama di tengah-Tengah Kemajemukan Masyarakat (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
In writing this article, the author used a descriptive qualitative method that tries to explain the role of church leaders in fostering interreligious harmony amidst the diversity of indonesian society. This article highlights the integral role played by church leaders in advancing interfaith harmony in indonesia, a society rich in ethnic, religious, racial, and cultural diversity. In the midst of this complexity, church leaders are not only spiritual figures, but also agents of developing understanding, tolerance and cooperation between religious communities. By teaching the values ​​of love, peace, forgiveness and respect, they shape their people's perspective on the importance of living peacefully with people of other religions. Apart from communicating these values ​​through sermons and teaching, church leaders are also a driving force in fostering inter-religious dialogue and campaigning messages of peace and tolerance. They emphasized that all religions are not a source of conflict, but rather wealth that can deepen the social and spiritual dimensions of society.Awareness of the importance of interfaith harmony and the active role of church leaders in strengthening it is crucial to ensuring harmony and progress in indonesia as a pluralistic country. Church leaders are not only responsible in the spiritual realm, but also play a key role in building a solid foundation for interfaith harmony in society. Reference sources, such as scriptures, journals, and theological sources, provide a credible foundation that supports the overall argument presented in this article.